Single intermediate vector boson production in e(+)e(-) collisions at root s=183 and 189 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (2001)
The cross sections for the production of single charged and neutral intermediate vector bosons were measured using integrated luminosities of 52 pb-1 and 154 pb-1 collected by the experiment at centre-of-mass energies of 182.6 GeV and 188.6 GeV, respectively. The cross sections for the reactions were determined in limited kinematic regions. The results found are in agreement with the Standard Model predictions for these channels. © 2001 Elsevier Science B.V.